Geological engineering problems associated with tunnel construction in karst rock masses: The case of Gavarres tunnel (Spain) - Alija, S.; Torrijo, F.J.; Quinta-Ferreira, M. (Engineering geology, 2013)
A representative example of the problems associated with the excavation and support of tunnels in karst ground is presented. It is a peculiar case in terms of heterogeneity and spatial distribution of zones of poor geotechnical quality, requiring the need to define, preferably in the study phases, adequate site investigation, suitable design procedures, efficient construction techniques and appropriate ground treatment. The difficulties associated with the instability of the karstified ground, and the presence of cavities, wholly or partially filled with soils of low cohesion, are discussed via retrospective analysis. The solutions adopted to solve the problems encountered during the tunnel construction enabled a systematic approach, useful for new construction projects in limestone terrains of medium to high karstification. •The design and construction of tunnels in karst areas is subject to problems.•We present a tunnel built in a karst area and the problems and proposed solutions.•Present proposals for future work in similar situations to the one discussed here•The validity of the solutions is shown in the successful completion of the tunnel.